The Moderating Role of Perceived Organisational Support in the Relationship between Employees’ Entrepreneurial Orientation and Organisational Commitment - Wójcik-Karpacz, Anna; Karpacz, Jarosław (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2020)
Objective: The purpose of this article is to analyse the moderating role of perceived organisational support (POS) in the relationship between employees’ entrepreneurial orientation (EEO) and organisational commitment (OC).Research Design & Methods: The research is aimed at determining the role of POS and EEO in explaining differences in employees’ commitment to a given organisation. The set of research proposals identifies (1) how employees’ entrepreneurial orientation and organisational commitment are related to each another and (2) how the relationship between employees’ entrepreneurial orientation and organisational commitment is moderated by perceived organisational support. The method used to carry out the quantitative empirical research was CAWI (Computer Assisted Web Interviews). The conceptual framework for this research was the theory of perceived organisational support. The project was funded by the National Science Centre in Poland (funds allocated on the basis of a decision no. DEC-2014/15/B/HS4/04326).Findings: The research provides knowledge about entrepreneurial personality in determining employees’ commitment to their organisation. At the same time, it identifies the role of POS as a moderator of the EEO-OC relationship.Implications / Recommendations: The results of the research allow for a better understanding of entrepreneurship and strengthen its theoretical foundations as an individual-level construct that determines organisational commitment. In addition, the description of the moderation effect (POS as a moderating variable) helps to better explain and predict the relationships between EEO and OC. Managers must pay more attention to the supportive organisational environment because of its effect on the strength of employees’ entrepreneurial orientation and its impact on their organisational commitment. The research results encourage further analyses on EO in vertical, horizontal and temporal dimensions in various size enterprises and their business profiles.Contribution: The article presents arguments which enable the recognition of employees’ entrepreneurial orientation as a determinant of organisational commitment and adding POS to the list of factors moderating the relationship between employees’ entrepreneurial orientation and organisational commitment. In addition, the research proves that the age of employees is positively related to their commitment to the organisation (the older they were, the more committed to the enterprise), while seniority is negatively related to organisational commitment (the more seniority employees had, the less committed they were).